Desensitisation of somatostatin, TRH and GHRH responses to glucose in the diabetic (Goto-Kakizaki) rat hypothalamus - Lewis, B.M.; Ismail, I.S.; Issa, B.; Peters, J.R.; Scanlon, M.F. (1996)
We have studied the effects of glucose on the release of somatostatin (SS), TRH and GHRH from incubated hypothalami of normal and genetically diabetic, Goto-Kakizaki (GK) rats. The active isomer D-glucose caused a dose-related inhibition of SS, TRH and GHRH from normal rat hypothalami over a 20-min incubation period in vitro. In contrast, in GK rats the effects of glucose on TRH and SS were significantly reduced and the effects on GHRH were abolished. These data indicate that the sensitivity of SS-, TRH- and GHRH-producing hypothalamic neurones is reduced in diabetic rats. The effect is most pronounced for GHRH release as there was no change in the release of this peptide with increasing glucose concentrations. In conclusion, it appears that the diabetic state in GK rats causes differential desensitisation (GHRH>TRH and SS) of neuronal responses to subsequent changes in glucose concentrations in vitro. This may be due to alterations in the neurotransmitter control and/or a reduction in number, affinity or function of glucose transporters on these peptidergic neurones or other intermediary neuronal pathways.